(untitled) (Revista horizonte, 2021)
Objective: to determine depression in the elderly, according to the geriatric scale of YESAVAGE, belonging to the different centers of practice of the Physical Education career, quantitative study of descriptive character of cross section, sample of intentional character, 118 elderly subjects, within of these 30 men and 88 women, from 8 centers of the city of Osorno, age range between 64 to 93 years. Methodology: for the data collection was used, the scale questionnaire of geriatric depression - Yesavage, which measures, level of depression in older adults, validated by the Pan American Health Organization. Results: Of the 118 subjects surveyed, 56.8% (67) presented a normal state without diagnosis of depression, 37.3% (44), presented a moderate depression and 5.9% (7) presented a state of severe depression, it is noteworthy that 6.8% (8) of older adults is already diagnosed with the symptoms of depression according to their doctors, according to the marital status of older adults operated can be noted that widows they present a greater state of depression. Conclusion: most of the elderly have a mild depression level, followed by a lower number with severe depression and that although all older adults spend at least 2 hours a week doing physical or recreational activity, the 43% present depression, this is due to the fact that the great majority lives without relatives and does not carry out any other activity.